'The Waldseemüller Map' - A Gift of Germany to the World. (1st August 2013) - France, Fenella G; Toth, Michael
Abstract : The Waldseemüller 1507 World Map was the first map (printed or manuscript) to refer to America. It is sometimes referred to as 'America's birth certificate' and was purchased by the Library of Congress in July 2001 from Germany. Johann Schöner (1477-1557), a Nuremberg astronomer-geographer had acquired an edition of the first printing, binding it into a volume with other maps. In 1901, Joseph Fisher, a Jesuit historian, who was conducting research in the library at Wolfegg Castle, Wurttenberg, Germany, discovered Schoner's book and the famous Waldseemuller Map. The copy at the Library of Congress is the only known survivor of the 1000 copies of the map believed to have been printed. Owing to the extreme rarity of this precious map, the Library of Congress undertook two major initiatives to ensure its preservation. The exchange between the German Government and the Library of Congress required that the map always be on exhibit for anyone to view, and a large anoxic visual display encasement was designed to maintain a 20-30 years' hermetic seal, protecting the document from environmental risks. Before to encasement for display, the Library conducted hyperspectral imaging to capture extensive historical information for access by researchers and scholars.